2020
DOI: 10.1093/jtm/taaa155
|View full text |Cite
|
Sign up to set email alerts
|

Use of face masks and other personal preventive measures by Hajj pilgrims and their impact on health problems during the Hajj

Abstract: Background The Hajj is one of the world’s largest pilgrimage and gathers millions of Muslims from different nationalities every year. Communicable diseases have been reported frequently, during and following the Hajj and these have been linked to individual behavioural measures. This study aimed to measure the effect of personal preventive measures, such as facemask use, hand hygiene and others, adopted by pilgrims in reducing the acquisition of infectious diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
(11 reference statements)
1
12
0
Order By: Relevance
“…These advices were applicable for either healthy pilgrims or vulnerable people living with specific diseases. Personal hygiene and facemasks were universal precautions as preventive measures in communicable diseases and have been proven to be effective in preventing disease transmission (Alasmari et al., 2020; Sahin et al., 2015). All pilgrims should make sure they are fully vaccinated prior to making the Hajj and should be ready with their vaccination cards (Alasmari et al., 2020; Memish et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These advices were applicable for either healthy pilgrims or vulnerable people living with specific diseases. Personal hygiene and facemasks were universal precautions as preventive measures in communicable diseases and have been proven to be effective in preventing disease transmission (Alasmari et al., 2020; Sahin et al., 2015). All pilgrims should make sure they are fully vaccinated prior to making the Hajj and should be ready with their vaccination cards (Alasmari et al., 2020; Memish et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A few studies reported the incidence of death as only 13.89% in this review. There was an incidence rate of about 44 deaths The most common communicable disease during the Islamic pilgrimage to Mecca was respiratory tract infection (Alasmari et al, 2020;Farahmand et al, 2022;Mushi et al, 2021). This was followed by several ambiguous infectious symptoms such as cough, fever, and sore throat.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous observational studies at Hajj have failed to show the effectiveness of facemasks in preventing respiratory infections [50][51][52], possibly due also to poor adherence to instructions, although a recent study showed that changing facemask every four hourly reduced the chance of upper respiratory tract infections among Hajj pilgrims (adjusted OR 0.56; 95% CI 0.34 to 0.92; p = 0.02) [55]. In our cRCT, though pilgrims in both intervention and control groups were close to each other day and night, none wore a mask for 24 hours as advised.…”
Section: Plos Onementioning
confidence: 95%
“…Although the incidence of TD has decreased in recent years, particularly in regions with growing economies [11], it remains a significant problem for international travellers. The reported incidence varies from 5.4% to 85% [12, 13] of travellers. It is intriguing to consider how COVID‐19 public health measures such as greater use of hand sanitisers may influence the incidence of TD, but an epidemiologic surveillance study from Spain did report a decrease in food and waterborne infections during year 1 of the pandemic [14].…”
Section: Traveller's Diarrhoeamentioning
confidence: 99%